Polypeptide Antibiotic Produced by a Thermo-Halophilic Bacterium from Pria Laot Sabang 76 Isolate - Febriani, Febriani; Suzanni, Mulia A.; Rakashiwi, Ellenia; Nurdin; Iqbalsyah, Teuku M. (Universitas Andalas, 2024)
Extremophiles are known to produce antibiotics. This study aimed to isolate and purify polypeptide antibiotics from Pria Laot Sabang (PLS) 76, a bacterium isolated from an undersea fumarole. The antibiotic production was done by cultivating PLS 76 in a 2.5% TSB liquid medium and incubated at 70°C, 150 rpm for 112 hours. Ninhydrin assay on the crude supernatant after centrifugation indicated that the PLS 76 produced a polypeptide antibiotic. The supernatant was partitioned using methanol. The antibiotic activity was tested using the Kirby-Bauer method, and the inhibition zone was about 12 mm against Escherichia coli and Staphylococcus aureus. The methanol fraction was purified further by Preparative Thin Layer Chromatography and produced several fractions. Fractions with the same Rf were pooled and subjected to the ninhydrin assay. Fraction A, which gave a positive result after the ninhydrin assay, showed an inhibition zone of only 7 mm against E. coli and S. aureus. The Quadrupole Time-of-Flight (QTOF) Mass Spectrometry data indicated that the antibiotic's structure was similar to Polymyxin B2, an antibiotic of a polypeptide group.